Fostering Florists in Bangun Sari Lama Village, Tanjung Morawa District, Deli Serdang Regency in Utilizing Social Media as an Effort to Increase Market Share - Ritonga, Alwi Dahlan; Amin, Muryanto; Junita, Agnes; Putri, Anggi Sefira Irwani; Sitinjak, Ericka Septeany; Kurniawan, Hansel Alif; Bella, Mera; Melanie, Mutiara; Ginting, Putri Adelia Br (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The florists in Bangun Sari Lama Village are still very dependent on the traditional model of selling which requires direct interaction between the seller and the buyer. Therefore, during the Covid-19 pandemic, sales turnover decreased drastically. In fact, if florists are able to take advantage of social media this problem can be handled. The implementation of this activity aims to provide guidance to florists regarding the use of media social media and the importance of creating a special website for Bangun Sari Lama village to facilitate online sales on line. The method of implementing this activity is done offline, namely socialization and sharing questionnaire to 20 respondents. In this activity, information was obtained that there are still many florists who lack working capital so that it has an impact on the quality of ornamental plants sold and then causes low levels of income and their ability to market their business.